EVIDENCE FOR A SINGLE-STRANDED ADENOVIRUS-ASSOCIATED VIRUS GENOME: FORMATION OF A DNA DENSITY HYBRID ON RELEASE OF VIRAL DNA - Rose, James A. (1969)
Extracted adenovirus-associated virus DNA is known to be double-stranded, and, therefore, it has been assumed that these virus particles contain a double-stranded genome. Recent findings, however, have suggested that the DNA in virus particles is equivalent to only half the molecular weight of extracted molecules. A density analysis of DNA extracted from a mixture of virus particles containing either bromodeoxyuridine-substituted or unsubstituted DNA shows that virions contain single-stranded DNA which, when released, forms duplex structures. A similar circumstance is as yet unknown among other viruses.